An Analysis on the Factors of English Learning Difficulties Faced by the Ninth Grade Student at SMP Swasta Banuhampu - Zafira, Annisa Fathin; Sakti, Genta (Lembaga Yasin AlSys, 2023)
This reasearch based on in the process of learning English. The problem was namely: “What are the factors of english learning difficulties for students in learning english? These problems were explained through observation and interviews with class IX students at SMP Swasta Banuhampu. In this study, researchers used qualitative research as a research methodology with a descriptive analysis research design. The research subjects were 21 students of the ninth grade and english teacher at SMP Swasta Banuhampu. Data obtained from observation and interviews. The results of this study inform that factors of students difficulties in learning english based on internal and eskternal factors. The researchers classify the problems they face from several factors of existing learning difficulties. The researcher group the problems from physiological factors into 2 general categories, namely: (1) pysical health (2) body defect. On psychological factors, the researcher group problems into 3 general categories, namely: (1)intelligence (2) interested (3) motivation. On the school factor, the researcher group problems into 3 general categories, namely: (1) parental support (2) noisy home atmosphere (3) economic problems. On school factors, the researcher group problems into 3 general categories, namely: (1) teaching method is not varied (2) english learning facilities are inadequate. On social factors, the researcher group problems into 2 general categories, namely (1) the living environment does not motivate to learn english, an (2) technological sophistication makes negligent in learning english.